A new separation approach of amylose fraction from gelatinized high amylose corn starch. (October 2022) - Zhu, Yuechun; Cui, Bo; Yuan, Chao; Lu, Lu; Li, Jianpeng
Abstract: This work aimed at developing a new method to separate amylose from high amylose corn starch (HACS) with calcium chloride (CaCl2 ) solution. The prepared amylose C was compared with the amylose N obtained with traditional sodium hydroxide (NaOH) solution. Although the extraction rate of purified amylose C (55.42 ± 0.53%) was slightly lower than that of purified amylose N (61.17 ± 0.60%), high performance size exclusion chromatography (HPSEC-MALLS-RI) patterns showed that it had higher purity. X-ray diffraction (XRD) and differential scanning calorimeter (DSC) results indicated that amylose C had more ordered and compact structure. In addition, the reagent solution consumption of amylose C was only about 30% of amylose N. Graphical abstract: Image 1 Highlights: A new method of separating amylose with calcium chloride solution was established. The purity of the amylose separated by calcium chloride solution was higher. The method consumed smaller volume of water.